Ab Initio Cyclic Voltammetry on Cu(111), Cu(100) and Cu(110) in Acidic, Neutral and Alkaline Solutions. Issue 22 (18th September 2019) - Bagger, Alexander; Arán‐Ais, Rosa M.; Halldin Stenlid, Joakim; Campos dos Santos, Egon; Arnarson, Logi; Degn Jensen, Kim; Escudero‐Escribano, María; Roldan Cuenya, Beatriz; Rossmeisl, Jan
Abstract: Electrochemical reactions depend on the electrochemical interface between the electrode surfaces and the electrolytes. To control and advance electrochemical reactions there is a need to develop realistic simulation models of the electrochemical interface to understand the interface from an atomistic point‐of‐view. Here we present a method for obtaining thermodynamic realistic interface structures, a procedure we use to derive specific coverages and to obtain ab initio simulated cyclic voltammograms. As a case study, the method and procedure is applied in a matrix study of three Cu facets in three different electrolytes. The results have been validated by direct comparison to experimental cyclic voltammograms. The alkaline (NaOH) cyclic voltammograms are described by H* and OH*, while in neutral medium (KHCO3 ) the CO 3 * species are dominating and in acidic (KCl) the Cl* species prevail. An almost one‐to‐one mapping is observed from simulation to experiments giving an atomistic understanding of the interface structure of the Cu facets. Atomistic understanding of the interface at relevant eletrolyte conditions will further allow realistic modelling of electrochemical reactions of importance for future eletrocatalytic studies. Abstract : Linking simulation to experiment : we present a method to move from thermodynamically realistic interface structures obtained from ab initio simulations to cyclic voltammograms and vice versa. The method is validated by direct comparison to experimental cyclic voltammograms, showing almost one‐to‐one mapping from simulation to experiment.